Research on Current-fed Switched-capacitor-based Multiple Modular DC Transformerand Its Optimized Modulation Strategy - SUN Qianhao; LI Yalou; MENG Jingwei; ZHAO Biao; MU Qing; ZHANG Xing (Kongzhi Yu Xinxi Jishu)
To solve the connecting issue of different medium-voltage DC (MVDC) buses in MVDC power grids, a current-fed switched capacitor-based input-series-output-series multiple modular DC transformer (CFSC-DCT) was designed in this paper. Compared with the traditional dual-active-bridge based DCT, CFSC-DCT has the key online redundant design and DC fault isolation capability from the view of topology, thus improving the reliability of MVDC power grid. Meanwhile, to optimize the current stress in high frequency link (HFL) of CFSC-DCT, a dual HFL voltage amplitudes matching modulation strategy (DAM) is employed for the proposed CFSC-DCT. Based on DAM, the HFL voltages of CFSC-DCT is always under the matching state and the HFL current stress can be optimized, solving the issue of DC terminal voltages mismatch caused by the traditional square-wave modulation, and improving the efficiency and economic benefit of DC transformer and MVDC power grid.